Odpowiedzi

2010-01-08T16:40:54+01:00
13e-5(f-3e)=13e-5f+15e=28e-5f

4(-2r+s)-10,5r=-8r+4s-10,5r=-18,5r+4s

-3(3x-2y)+2(x-2y)=-9x+6y+4x-4y=-5x+2y

-5(2z-3y)-4(4z-2y)=-10z+15y-16z+8y=-26z+23y

2(2p-3y)-4(4z-2y)=4p-6y-16z+8y=4p+2y-16z

2(3x²-2y+5y²)-3(4y+5y²)+2x-3x²=
=6x²-4y+10y²-12y-15y²+2x-3x²=3x²-5y²+2x-16y




Najlepsza Odpowiedź!
2010-01-08T16:41:12+01:00
13e-5(f-3e)= 13e - 5f + 15e = 28e - 5f
4(-2r+s)-10,5r= -8r + 4s - 10,5r = -18,5r + 4s
-3(3x-2y)+2(x-2y)=-6x + 6y + 2x - 4y = -4x + 2y
-5(2z-3y)-4(4z-2y)= -10z + 15y - 16z + 8y = -26z + 23y
2(2p-3y)-4(4z-2y)= 4p - 6y - 16z + 8y = 4p + 2y - 16z
2(3x²-2y+5y²)-3(4y+5y²)+2x-3x²= 6x² - 4y + 10y² - 12y - 15y² + 2x - 3x² = 3x² - 5y² - 16y + 2x
2010-01-08T16:50:26+01:00
13e-5(f-3e) = 13e-5f+15e = 28e-5f
4(-2r+s)-10,5r = -8r+4s-10,5r = -18,5r+4s
-3(3x-2y)+2(x-2y) = -9x+6y+2x-4y = -7x+2y
-5(2z-3y)-4(4z-2y) = -10z+15y-16z+8y = -26z+23y
2(2p-3y)-4(4z-2y) = 4p-6y-16z+8y = 4p+2y-16z
2(3x²-2y+5y²)-3(4y+5y²)+2x-3x² =6x²-4y+10y²-12y-15y²+2x-3x² = 3x²-5y²-16y+2x